2008 2nd International Conference on Bioinformatics and Biomedical Engineering 2008
DOI: 10.1109/icbbe.2008.248
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative and Binding Effect of Nano-TiO2 on Plasmid DNA and Pepsin

Abstract: With the development of nano material industry, more and more attention has been paid on the biological effect of nano materials. However, little research focused on the effect of nano TiO 2 on protein level. In this study, we detected the toxic effect of nano TiO 2 (50~60nm) on DNA and functional proteinase. The oxidative damage of nano TiO 2 on DNA was detected by gel electrophoresis and HPLC. Anson method was used to study the inhibition of nano TiO 2 on pepsin, and the mechanism of the reaction was further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Previous studies in various animal and human cell lines demonstrated that TiO 2 nanoparticles generate a large amount of hydroxyl free radicals, thereby leading to DNA damage 41,42. It has been proposed that the genotoxicity of metals and metal oxides results from the indirect formation of ROS.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in various animal and human cell lines demonstrated that TiO 2 nanoparticles generate a large amount of hydroxyl free radicals, thereby leading to DNA damage 41,42. It has been proposed that the genotoxicity of metals and metal oxides results from the indirect formation of ROS.…”
Section: Discussionmentioning
confidence: 99%
“…() reported that TiO 2 nanoparticles enhance photocatalysis, oxidative stress, DNA adducts, DNA strand breaks and chromosome damage. Earlier reports in animal cells have also suggested that TiO 2 nanoparticles generate a large amount of hydroxyl free radical thereby leading to DNA damage (Reeves et al ., ; Zhu et al ., ; Ghosh et al ., ). In our study, the DCFHDA assay in human lymphocyte cells also suggested a significant increase in ROS generation with an increase in treatment concentration.…”
Section: Discussionmentioning
confidence: 99%